MECHANICAL BEHAVIOR OF THE BENTONITE MIXED-KAOLIN AND SAND - Agus Setyo Muntohar (Civil Engineering Dimension, 2010)
Understanding characteristics of soil mixtures lead to increasing the confidence level before applying such materials in the field. The outcomes of this study can provide insight into mechanical behaviour of a soil mixture between non-swelling and bentonite soil. Series of laboratory tests were conducted to evaluated index properties, compaction, strength, and swelling behaviour of the soil – bentonite mixtures. The result of this study indicated that the existence of bentonite in the soil mixtures influence the swelling behaviour, which follows hyperbolic curve model. Amount and size of non swelling fraction reduced the swelling and compressibility of expansive soils.